Factors Affecting Financial Stability of Sharia Banks in Indonesia - Ulfi Kartika Oktaviana; Titis Miranti (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
To ensure the financial stability of Indonesian banks, especially Sharia banks, it is essential to focus on various factors and elements. This study investigates the endogenous and exogenous factors influencing the financial stability of Sharia banks in Indonesia. The study utilized data from the annual financial statements of Sharia banks in Indonesia spanning from 2010 to 2021. Panel data regression served as the analytical tool for the research. The findings indicate that the stability of Sharia commercial banks in Indonesia is influenced by both capital structure and credit risk. Financial leverage also affects sharia bank’s financial stability. While ownership distinguishes a bank in terms of organizational structure, it does not necessarily guarantee stability. Islamic commercial banks remain stable amid the COVID-19 pandemic, showing no significant impact on their overall stability. These findings will enhance bank understanding of the risks faced by banks and form the basis for new regulatory efforts to strengthen overall risk management, including liquidity risk and credit risk.